Body image among Muslim women in Israel: exploring religion and sociocultural pressures. Issue 10 (25th November 2020) - Sidi, Yael; Geller, Shulamit; Abu Sinni, Aline; Levy, Sigal; Handelzalts, Jonathan E.
ABSTRACT: The study aimed to investigate the association of the Muslim religion, as a multidimensional factor, with social pressures related to body image concerns, among Muslim women in Israel. Four hundred and Seventy-five Israeli Muslim women ages between 18 and 30 years completed questionnaire measures of strength of religious faith, wearing a traditional head cover (the Hijab), positive and negative body image, media exposure, societal pressures to conform to Western body ideals and its internalization, from 2016 to 2018. Strength of religious faith and wearing the Hijab were positively associated with positive aspects of body image, while only strength of religious faith negatively correlated with body dissatisfaction. Further, mediation analyses revealed that the relationship between the strength of religious faith and both positive body image and body dissatisfaction was mediated by media pressures. Notably, reduced peer pressures had more influence on positive body image, while reduced family pressures were more influential for negative body image. These results are discussed with regard to promoting a more intricate and multicultural understanding of body image concepts.